First measurement using a nuclear emulsion detector of the νμ charged-current cross section on iron around the 1 GeV energy region. (13th March 2021) - Oshima, H; Matsuo, T; Ali, A; Aoki, S; Berns, L; Fukuda, T; Hanaoka, Y; Hayato, Y; Hiramoto, A; Ichikawa, A K; Kawahara, H; Kikawa, T; et al.
Abstract: We have carried out ν_μ charged-current interaction measurement on iron using an emulsion detector exposed to the T2K neutrino beam in the J-PARC neutrino facility. The data samples correspond to 4.0 × 10^19 protons on target, and the neutrino mean energy is 1.49 GeV. The emulsion detector is suitable for precision measurements of charged particles produced in neutrino–iron interactions with a low momentum threshold thanks to a thin-layered structure and sub-μ m spatial resolution. The charged particles are successfully detected, and their multiplicities are measured using the emulsion detector. The cross section was measured to be σ^Fe_CC = (1.28 ± 0.11(stat.)^+0.12_-0.11(syst.)) × 10^-38 cm^2/nucleon . The cross section in a limited kinematic phase space of induced muons, θ_μ < 45^° and p_μ > 400 MeV/c, on iron was σ^Fe_CC 1mm phase 0.5mm space = (0.84 ± 0.07(stat.)^+0.07_-0.06(syst.)) × 10^-38 cm^2/nucleon . The cross-section results are consistent with previous values obtained via different techniques using the same beamline, and they are reproduced well by current neutrino interaction models. These results demonstrate the capability of the detector in the detailed measurement of neutrino–nucleus interactions around the 1 GeV energy region.